Does the theory of constraints in supply chain management really matter? An assessment of the impacts of the TOC in the redesign of a supply chain - Stefano, Gustavo da Silva (Universidade do Vale do Rio dos Sinos, 2020)
In a world with increasing complexity, a challenging scenario and greater competition many companies still feel that their supply chains do not have the competencies required to prosper within such environment. In fact, old supply chain problems are still current challenges for many organizations. Therefore, supply chain management (SCM) and supply chain redesign plays a strategic role for this context, demonstrating distinctive goals and results such as cost reduction, lower inventory levels and bullwhip effect minimization. The supply chain redesign proposals are based on diverse methodologies, such as Just-In-Time, lean manufacturing practices and the Theory of Constraints. Among those methodologies, the Theory of Constraints (TOC) proposes a solution for the supply chain that aims to increase the throughput of sales, while reducing inventories at the same time. Within the SC context, however, TOC research lacks a conceptual model or method for application of its practices, have an absence of studies that evaluate consistently the implementation of its performance measures, and have a deficiency of empirical evidence to support its improvements. Thus, this research aims to fulfill those gaps by utilizing a simulation model of a real empirical case to apply the TOC supply chain replenishment system (TOC SCRS) steps. Using system dynamics to create the base model, other scenarios are created replicating the gradually implementation of the TOC in the system. Inventory levels, throughput and the IDD are measured for each scenario and compared to understand the benefits and their respective significance. Thus, the causal impact analysis is utilized in order to compare the different scenarios with the base model, as well as to compare the scenarios among themselves. The results and the findings are presented and discussed, and the contributions are detailed in both empirical and academic contexts. The conclusion sums up the research and present future venues of studies that can derive from this research.
Keywords: Theory of constraints; Supply chain management; System dynamics modeling; Causal impact; Supply chain replenishment system; Teoria das restrições; Gestão da cadeia de suprimentos; Modelagem de dinâmica de sistemas; Impacto causal; Sistema de reabastecimento da cadeia de suprimentos; ACCNPQ::Engenharias::Engenharia de Produção